2014
DOI: 10.1080/09205063.2014.923368
|View full text |Cite
|
Sign up to set email alerts
|

Improved small molecule drug release fromin situforming poly(lactic-co-glycolic acid) scaffolds incorporating poly(β-amino ester) and hydroxyapatite microparticles

Abstract: In situ forming implants are an attractive choice for controlled drug release into a fixed location. Currently, rapidly solidifying solvent exchange systems suffer from a high initial burst, and sustained release behavior is tied to polymer precipitation and degradation rate. The present studies investigated addition of hydroxyapatite (HA) and drug-loaded poly(β-amino ester) (PBAE) microparticles to in situ forming poly(lactic-co-glycolic acid) (PLGA)–based systems to prolong release and reduce burst. PBAEs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
11
1
Order By: Relevance
“…It was initially observed that PβAEs synthesized using single step approach were unstable in ethanol. This was different from previously reported data, where ethanol was used as a stable washing solvent . Originally, it was believed that degradation was due to the water content in the solvent.…”
Section: Discussioncontrasting
confidence: 83%
“…It was initially observed that PβAEs synthesized using single step approach were unstable in ethanol. This was different from previously reported data, where ethanol was used as a stable washing solvent . Originally, it was believed that degradation was due to the water content in the solvent.…”
Section: Discussioncontrasting
confidence: 83%
“…For example, in-situ forming implants (ISFIs) have a dual-release pattern with a large undesirable burst release, which may cause major toxicity problems and consume the loaded drug in the implants rapidly 10 . Designing this type of implants with a minimum initial burst release becomes an attractive challenge, and one of the key issues in the design of ISFIs 11 . Moreover, some drug-loaded implants can be designed in a controlled way to have a dual-release profile to release a large amount of drug early, i.e., burst release, to rapidly reach the effective therapeutic concentration at the target site while keeping drug concentration within the effective level during the sustained release phase 12 .…”
Section: Modelling Of Combination Therapy Using Implantable Anticancementioning
confidence: 99%
“…For microspheres, PLGA is considered to be a good drug carrier owning to its excellent biocompatibility and biodegradability [16,17]. However, PLGA microspheres provide a large initial burst release [18]. Therefore, to overcome this problem, polymers such as poly(β-amino ester) (PBAE) [18], polyethylene glycol (PEG) [19], and poly(L-lactic acid) (PLLA) [20] were added to adjust the release profile of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…However, PLGA microspheres provide a large initial burst release [18]. Therefore, to overcome this problem, polymers such as poly(β-amino ester) (PBAE) [18], polyethylene glycol (PEG) [19], and poly(L-lactic acid) (PLLA) [20] were added to adjust the release profile of the drug. Inorganic porous materials were also used as bone substitutes, such as α-tricalcium phosphate (α-TCP) [21], β-tricalcium phosphate (β-TCP) [2224], and hydroxyapatite (HA) [18].…”
Section: Introductionmentioning
confidence: 99%